Mathematical Simulation of Isotope Exchange in Flexible Manufacturing Systems with Electrochemical Phase Flux Reversal; Russian Physics Journal; Vol. 67, iss. 3 - Dorofeeva (Dorofeyeva) L. I. Liudmila Ivanovna (2024, 2024)
Title screen